Personality traits and their relationship to burnout among football coaches - Morsi, L.Dr. Marwa Omar (Sulaimani Journal for Humanities, 2025)
Coaching is an extremely demanding profession, requiring individuals with strong personal and psychological qualities to effectively lead their teams and players, manage club management and fans, and withstand the psychological pressures they face. This enables them to make sound and accurate decisions. A lack of these positive attributes can expose them to psychological stress, negatively impacting their job performance and potentially their social and health well-being. This research highlights the importance of identifying the personality traits of the coaches (the research sample) and determining their burnout levels. It also explores the relationship between these traits and burnout, which can be leveraged to enhance the skills of coaches, who are crucial to the development of the game. The research aims to identify the personality traits and burnout levels of football coaches in Premier League clubs. The researcher utilized the Cattell Personality Inventory, a comprehensive and accurate test that measures sixteen personality traits, thus providing insights into the coaches' personalities.
Keywords: Personal characteristics; psychological expertise; coaches; football